Combining immunofluorescence with immunoblot assay improves the specificity of autoantibody testing for myositis. (4th February 2019) - Infantino, M; Tampoia, M; Fabris, M; Alessio, M G; Previtali, G; Pesce, G; Deleonardi, G; Porcelli, B; Musso, M; Grossi, V; Benucci, M; Manfredi, M; et al.
Abstract: Objective: Immunoblot (IB) methods are widely used to detect myositis-specific autoantibodies (MSAs); however, false-positive results are common. In this study, we aimed to determine whether associating the anti-nuclear antibody (ANA) IIF pattern may help to improve the specificity of MSA detection by IB in patients with idiopathic inflammatory myositis (IIM). Methods: Serum samples from 104 patients presenting with muscle weakness/myalgia and positive to at least one MSA by IB (MYOS12 Diver and MIOS7 Diver, D-tek) were tested for ANAs on HEp-2000 cells (Immuno Concepts). The chi-square test was used to analyse the concordance of the MSA result and its corresponding pattern by ANA testing between patients with and without IIM. Results: Eighty-three of the 104 patients had a diagnosis of definite IIM, while in 21 cases, patients were affected by other autoimmune diseases or various non-systemic diseases. Forty nine of 83 (59%) patients in the IIM group and 4/21 (19%) in the non-IIM group showed a concordance between ANA pattern and MSAs by IB ( P < 0.001). MSA monopositivity was significantly associated with IIM (91.6%) compared with 61.9% in the non-IIM group ( P = 0.0005). Conclusions: Considering both the MSA result and its corresponding pattern by ANA testing may help to improve the specificity of MSA detection by IB and to confirm the diagnosis of MSA-associated IIM. The monopositivity of MSAs is an important additional tool to validate IB results.